الفلسفة التسویقیة لشركات التسویق الهرمي المزعوم في ظل نضوج الفكر التسویقي وتكامل المزیج التسویقي الحدیث - غیاط, شریف (Finance and Business Economies Review, 2018)
This study is an attempt to research the reality of newly deployed pyramid marketing companies, which are heavily active in the presence of a suitable medium for the nature of fraudulent activity in virtual social networking sites. From this endeavor, the development of marketing thought and the maturity of marketing philosophy will be highlighted taking into account all the constructive dimensions of marketing, trade, society and the environment, as well as trying to bring down marketing companies to identify their marketing mix and knowledge and thus judge their marketing philosophy.